Postoperative Recovery Outcomes for Obese Patients Undergoing General Anesthesia: A Meta-Analysis of Randomized Controlled Trials - Hu, Zhen-Hua; Liu, Zhe; Zheng, Gai-Fang; Li, Zhan-Wen; Liu, Sheng-Qun (Frontiers in Surgery, 2022)
Purpose: This study was performed to assess the postoperative recovery outcomes in obese patients undergoing general anesthesia. Methods: The eligible studies were identified from PubMed, EmBase, and the Cochrane library until December 2020. The standard mean differences (SMDs) with 95% confidence intervals (CIs) were used to calculate the role of desflurane, sevoflurane, and propofol on recovery outcomes, and the analyses using the random-effects model. Results: Eleven randomized controlled trials involved 713 obese patients undergoing general anesthesia were selected for final meta-analysis. We noted desflurane was associated with shorter time to eye opening than sevoflurane (SMD: -0.86; 95%CI: -1.43 to -0.28; P=0.003). The use of desflurane with shorter time to extubation as compared with propofol (SMD: -1.13; 95%CI: -1.52 to -0.73; P<0.001) or sevoflurane (SMD: -1.19; 95%CI: -2.15 to -0.22; P=0.016), while sevoflurane was associated with longer time to extubation as compared with propofol (SMD: 1.47; 95%CI: 1.03 to 1.91; P<0.001). Desflurane were associated with shorter time to stating name as compared with propofol (SMD: -1.40; 95%CI: -2.32 to -0.48; P=0.003) or sevoflurane (SMD: -2.09; 95%CI: -3.33 to -0.85; P=0.001). In addition, desflurane was associated with longer time for orientation to place as compared with propofol (SMD: 0.65; 95%CI: 0.22 to 1.07; P=0.003), while desflurane with shorter time for orientation to place as compared with sevoflurane (SMD: -0.88; 95%CI: -1.46 to -0.30; P=0.003). Conclusions: The use of desflurane could provide better recovery outcomes in obese patients undergoing general anesthesia. Further large-scale trials should be comparison the long-term effectiveness of varies anesthetics.